Randomised controlled trial of an interactive multimedia decision aid on benign prostatic hypertrophy in primary care - Murray, Elizabeth (BMJ, 2001)
OBJECTIVE: To determine whether a decision aid on benign prostatic hypertrophy influences decision making, health outcomes, and resource use. DESIGN: Randomised controlled trial. SETTING: 33 general practices in the United Kingdom. PARTICIPANTS: 112 men with benign prostatic hypertrophy. INTERVENTION: Patients' decision aid consisting of an interactive multimedia programme with booklet and printed summary. OUTCOME MEASURES: Patients' and general practitioners' perceptions of who made the decision, decisional conflict scores, treatment choice and prostatectomy rate, American Urological Association symptom scale, costs, anxiety, utility, and general health status. RESULTS: Both patients and general practitioners found the decision aid acceptable. A higher proportion of patients (32% v 4%; mean difference 28%, 95% confidence interval 14% to 41%) and their general practitioners (46% v 25%; 21%, 3% to 40%) perceived that treatment decisions had been made mainly or only by patients in the intervention group compared with the control group. Patients in the intervention group had significantly lower decisional conflict scores than those in the control group at three months (2.3 v 2.6; −0.3, −0.5 to −0.1, P<0.01) and this was maintained at nine months. No differences were found between the groups for anxiety, general health status, prostatic symptoms, utility, or costs (excluding costs associated with the video disc equipment). CONCLUSIONS: The decision aid reduced decisional conflict in men with benign prostatic hypertrophy, and the patients played a more active part in decision making. Such programmes could be delivered cheaply by the internet, and there are good arguments for coordinated investment in them, particularly for conditions in which patient utilities are important.